PENGARUH MEDIA PUZZLE DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II UPTD SDN 122380 PEMATANG SIANTAR - ButarButar, Susi; Sirait, Jumaria; Siagian, Asister (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2024)
The purpose of this research is to determine the effect of puzzle media in improving the beginning reading abilities of class II students at UPTD SDN 122380 Pematang Siantar. This research is a quantitative research with a Pre-Experimental Design type with a One Group Pretest-Posttest research design (Preliminary Test – Final Test in a single group). In this study, only one research class was used. The sample for this research was class II, totaling 28 students with a sampling technique using Quota Sampling, which is a non-random sampling technique. Based on the results of data analysis and hypothesis testing that has been carried out, it is clear that there is an influence of puzzle media in improving students' initial reading abilities. It can be seen from obtaining a significant value (2-tailed) smaller than 0.05 (0.00 < 0.05) and a tcount value greater than ttable (14.441 > 2.056), then H0 is rejected and Ha is accepted. So it can be concluded that puzzle media has an influence in improving students' initial reading skills in class II UPTD SDN 122380 Pematang Siantar.